Süreç yönetiminde kritik süreçlerin belirlenmesi ve bir uygulama - Köken, Koray (My University, 2000)
Rekabet ve gelişen müşteri beklentilerinin günümüzde vazgeçilmez kıldığı en önemli unsur, değişimdir. Küreselleşen iş dünyasında, başarı ve kalıcılığı sürdürebilmenin yolu değişimi yönetmek ve etkin bir şekilde yönlendirebilmekten geçmektedir. Özellikle son on yıl içerisinde dünyada ve ülkemizde meydana gelen hızlı gelişmeler organizasyonların, değişimi destekleyen yeni yönetim sistemlerine sahip olmaları gerekliliğini doğurmaktadır. Organizasyonlarda değişim için gerekli esnekliğin sağlanabilmesi için, iş süreçlerinin, fonksiyonel yapılanma ve karar mekanizmalarının getirdiği tüm kısıtlamalardan kurtularak gerekli iyileşme ve sıçramayı sağlayacak şekilde geliştirilmesi gerekmektedir. Bu ise, şirketlerdeki süreçlerin sistematik bir şekilde incelenip, geliştirilmesi ve bu doğrultuda yapılandırılması ile, yani süreç odaklı yönetim ile mümkün olmaktadır. Süreç odaklı yönetimde amaçlanan, fonksiyonel birimlerin süreç temelinde entegrasyonu ile kalite, maliyet ve zaman faktörlerinin müşteriye yönelik olarak, şirket rekabet gücünü arttıracak şekilde optimizasyonudur. Bu tez çalışmasında Süreç Yönetimi'ne hem teorik hem de pratik açıdan yaklaşılmış, fakat ağırlık olarak kritik süreçlerin belirlenmesi ve süreç yönetiminin şirketin rekabet gücünü arttırması konuları üzerinde durulmuştur. konu ile ilgili temel kavram ve tanımlamalara yer verilmiştir. Ayrıca Süreç Yönetiminin tarihsel gelişimi ve EFQM modelinin süreç yönetimine yaklaşımı konuları işlenmiştir. İkinci Bölüm'de Süreç Yönetimi'nin uygulama aşamaları en başndan sonuna kadar detaylı bir şekilde ele alınmıştır. Üçüncü Bölüm'de süreç geliştirmenin ayrılmaz bir parçası olan süreç performansına ve ölçümüne değinilmiş, örnek ölçüm kriterleri gösterilmiştir. Dördüncü Bölüm'de de Borusan Birleşik Boru Fabrikaları'nda uygulanmakta olan Süreç Yönetimi ve Süreç İyileştirme çalışmaları incelenmiştir.

Market economics forces the companies to change. So the question is how to change. The goal of change is almost always the same: increased ability to compete through cost reduction. What is needed is an organization that is customer-focused and market-driven in its external relations, and proces-focused and team-oriented in its internal relations. Only, such an organization can look at the way work is performed across functional operations more logical, effective and efficient. Such an effort is at the heart of Process Management. Process Management approach is based on Total Quality Management (TQM), as the management and continuous improvement of processes is a fundamental component of TQM approach. Process management ensures that process outputs meet the requirements of customers, internal or external to the organization. Process Management activities are directed at establishing ownership responsibilities, defining the prosess, managing supplier-customer relationships, and evaluating process performance. Process Management provides long-term accountability forensuring that the process meets customer requrements and for managing the improvement of its performance.Process Management activities aim at increasing value of customers or otherwise improving process performance, typically in terms of lower cost, timeliness, higher reliability, or lower defect rates. Principles of Process Management: * Combine several jobs into one; don't view processes in departmental terms * Allow workers to make decisions * Perform process steps in natural order; begin with customer and work back * Perform work where it makes most sense * Reduce checks and controls; minimize the influence of bureaucracy Typical Result of Successful Process Improvement Program: * Work units shift from functional departments to process teams * The focus of performance measures shifts from activity to results * Performance gives way to ability as an advancement criteria. * Values shift from protective to productive * Manager leave off supervising and begin coaching * Hierarchical organization structures are flattened. * Executive responsibility shifts from scorekeeping to leading Many of today's processes evolved by growing with business, often as a series of decisions made by functional groups with little worry about cross-functional effectiveness. Many of these processes were first established before dramatic advances that occurred during the last decade in quality, computers, communication, and global competition. In past, processes were focused on control and efficiency. To survive in today's competitive enviroment, processes must be geared towards; * Quality and service to meet the neds of customers * Reduction in cost, interval, failures and defect rates * Innovation and flexibility * Increases in revenue and customer loyalty This thesis is divided into four sections. In Section 1, the main concepts and definitions of Process Managemet is given, also historical improvement of Process Management and EFQM approach to processes are explained. In Section 2, the steps of Process Management are given in detail. In Section 3, Process Performance Measurement, which is so vital to managing iand improving processes are explained. In Section 4, an application of Process Managemet in Borusan Birleşik Boru Fabrikaları is given. To ensure competitive advantage over a long term, process improvement should be done on a repeated basis. The company should position itself to change its processes quickly whenever there is an advantage in doing so.
Keywords: YÖNETİM